P2 Outcomes in adults following anatomic repair of congenitally corrected transposition of the great arteries. (2nd March 2016) - Arif, Sayqa; Bowater, Sarah; Clift, Paul; Thorne, Sara; Hudsmith, Lucy
Abstract : Introduction: Anatomic repair (double switch operation) for congenitally corrected transposition of the great arteries (ccTGA) is associated with good short to mid-term outcomes. An increasing number of these patients are surviving to adulthood. There is a paucity of data in adults regarding late sequelae. We sought to determine the long-term outcomes in older patients who have previously undergone a double switch operation for ccTGA. Methods: A retrospective analysis of 16 patient records from 2001 to 2015 from a single institution was conducted. Median age was 23 years (range 18–56 years, 14 male). Six patients had undergone a Senning-arterial switch and 10 patients underwent a Rastelli-Senning procedure. Associated defects included VSD (n = 13), pulmonary stenosis (n = 2) and pulmonary atresia (n = 13). Three patients had undergone prior pulmonary artery banding and 7 patients systemic-pulmonary artery shunting. We determined freedom from re-operation/intervention, development of systemic left ventricular (LV) dysfunction, systemic mitral regurgitation, conduction disorders and arrhythmias. Results: Median follow-up was 19 years (18–21 years). Eleven patients required further surgery with 4 patients having undergone two subsequent operations. Following anatomic repair, median time to 1 st operation was 11 years (7–13 years). Indications for re-operation included re-do RV-PA conduit in the Rastelli-Senning patients (n = 8) and aortic valve replacement in the Senning-arterial group (n = 3). 5 patients developed atrio-ventricular conduction block requiring a pacemaker. Three patients developed atrial arrhythmias, with 2 requiring ablation procedures. Six patients developed LV dysfunction. There were no deaths or need for cardiac transplantation in this series. Conclusion: The majority of patients required a second operation, largely in the Rastelli-Senning group. In the Senning-arterial group, late aortic valve insufficiency occurred in 50% of the patients. Conduction disease and atrial arrhythmias contribute to late morbidity in these patients. Nevertheless, the majority of patients are free of heart failure. Despite good short-term outcomes and survival following anatomic repair, careful long-term evaluation for structural and electrophysiological abnormalities is required.